2006
DOI: 10.1002/ejic.200500769
|View full text |Cite
|
Sign up to set email alerts
|

Ionic Liquids: Synthesis and Characterisation of Triphenylphosphonium Tosylates

Abstract: Ionic liquids are currently attracting considerable interest from chemists, partly due to their potential as “green” alternatives to volatile molecular organic solvents. Phosphonium ionic liquids have received much less attention than ammonium salts in the past, but the situation is changing. The salts are applied in the liquid state but in this work, salts with higher melting points than is generally the case are investigated. They are solid at room temperature, thus enabling facile separation of liquid react… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…While attention has been devoted to ILs based on quaternary nitrogen, studies related to ILs based on quaternary phosphorous cations are still few. It has been demonstrated that some phosphonium based ILs have better properties than nitrogen-based ILs, [ 29 , 30 ]. In fact, research on nanocomposites containing clay minerals modified with phosphonium based ILs has recently increased [ 31 , 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…While attention has been devoted to ILs based on quaternary nitrogen, studies related to ILs based on quaternary phosphorous cations are still few. It has been demonstrated that some phosphonium based ILs have better properties than nitrogen-based ILs, [ 29 , 30 ]. In fact, research on nanocomposites containing clay minerals modified with phosphonium based ILs has recently increased [ 31 , 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…For structures of similar triphenylphosphonium compounds, see: Bonnet & Kariuki (2006) and Ibrahim et al (2011). For uses of triphenylphosphonium compounds in synthesis, see: Liang (2015).…”
Section: Structure Descriptionmentioning
confidence: 99%
“…Phosphonium ionic liquids have been studied to a lesser extent although they possess some advantages over imidazolium ionic liquids. Phosphonium ionic liquids can be prepared without halide contamination, which is an important factor for the halogen‐sensitive reagents 6,7. Furthermore, phosphonium ionic liquids are more thermally stable than imidazolium and quaternary ammonium salts 8,9.…”
Section: Introductionmentioning
confidence: 99%